A Multidimensional Model of Analysis of Students' Global Experience in Higher Education - Maria José Sá (MDPI AG, 2023)
In the current higher education context, higher education institutions need, more than ever before, to compete for students, attracting, retaining and, ultimately, graduating them. To this end, actions are increasingly developed, and conditions are created to promote student success. The literature demonstrates that there is a strong link between the students' experience and success. However, students' experience cannot be controlled by the higher education institution, given the existence of previous subjective experiences that students bring when they enroll in higher education, which act as filters of their current experiences. The central goal of this study is to unveil the factors that students perceive as influencers on their global experience in higher education, which are reflected in their path, performance and success. The methodology used is qualitative, with in-depth interviews with students and institutional leaders from four Portuguese higher education institutions, complemented with documentary analysis. The results reveal that individual and organizational factors, alongside the students' global experience, clearly influence their definition of a successful higher education student. Students build their representations of success based on the multiplicity and complexity of their experiences in higher education, affected by the features of the higher education institution and mediated by their personal history and life project.